CAMX 2014 : October 13-16, 2014, Orlando, FL. (Society of the Advancement of Material and Process Engineering, 2014)
ACMA and SAMPE, the two leading composites and advanced materials industry organizations for nearly 60 years, have created a new event that connects and advances all aspects of the world's composites and advanced materials communities. CAMX the Composites and Advanced Materials Expo was held October 13-16, 2014 in Orlando, FL.
Keywords: Composite materials -- Congresses.; Materials -- Congresses.; elektronické knihy; electronic books